Analysis Into Extra Oral Features of Completely Edentulus Patients Pre and Post Complete Denture Treatment - Ashwin Kumar.S.P1 , Suresh Venugopalan2 , Sreedevi Dharman3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background :Edentulism has been a serious public health problem in industrialized countries due to the ageof the population , life quality and nutrition intake are impaired . Which is restored by the use of completedentures. Aim : To assess extra oral features of complete edentulous patients pre and post complete denturetreatment .Materials and method :Data of complete denture patients was screened and collected fromthe dental archives database and assessed the documentation evidences.Results :According to the study inComplete denture fabrication BPS showed aesthetically better post operative extra oral features comparedto the conventional method (p value < 0.05 significant [chi-square test]).Conclusion :Within the limitationof the study ,it is evident that BPS has shown better post operative aesthetic results compared to that of thepre op than the conventional CD. The extra oral features of a complete denture patient are enhanced whileusing a BPS type of a complete denture.